Anatomy of Muslim Women's Clothing in the Qur'an: Study by Maudhu'i Abdul Hayy Al Farmawi - Romziyana, Lutviyah; Hasanah, Mamluatul (JURNAL ISLAM NUSANTARA, 2024)
Islam encourages its people to invest while still paying attention to the principles, ethics, and sharia economic law. Increasing investor interest in Islamic stocks prompted the IDX to launch Islamic stock indices including the IDX-MES BUMN 17. In using the appropriate methods needed to avoid large losses, including through fundamental analysis. This study aims to examine the effect of ROE, PBV, DER, CR, and TATO on sharia stock prices that are incorporated in the BUMN 17 IDX-MES index. The research data is in the form of quarterly data sourced from the financial reports of 17 BUMN companies for the period January 2019 - December 2022. The method used is multiple linear regression analysis with SPSS tools. The results showed that ROE did not have a significant and positive effect on the share price of the IDX-MES SOE 17 sharia index. Meanwhile, the variables PBV, DER, CR and TATO had a positive and significant effect on the share price of the SOE IDX-MES sharia index 17. Simultaneously ROE, PBV, DER, CR and TATO have a significant effect on the share price of the IDX-MES BUMN 17 sharia index with a coefficient of determination (R2) of 75.9%